APPLICATION OF BIOWASTE MATERIALS FOR THE SoRPTION OF HEAVY METALS IN CONTAMINATED AQUEOUS MEDIUM (Biological Sciences - PJSIR, 2002)
Biowaste materials were evaluated as metal ion adsorbents in aqueous medium. The biowastes used  were  black gram husk, wheat bran, sheesham (Dalbergia sissoo) sawdust, pea pod , rice husk and  cotton  and  mustard  seed  cakes. All these biosorbents, except pea pod and rice husk, exhibited good adsorption potential  for Cd, Pb, Cu, Zn and Ni. Black  gram husk (bgh) was found to have the highest sorption capacity with 100, 99.4, 95.7, 98.2 and 93.1% removal of Cd, P_b, Cu, Zn and Ni, respectively. The metal ions adsorbed by bgh desorbed with 0.1 M HCl and the regenerated btosorbent was reused successfully for the sorption of metal ions in the next cycle. Concentration of the tested metals achieved at equilibrium in the contaminated aqueous medium was well below the maximum limits recommended  by  UNEP for sewage discharge. The study indicates the potential of bgh as a new, inexpensive and efficient  biosorbent  for the  treatment  of water  contaminated  with  heavy metals.